Catheter ablation of persistent atrial fibrillation. (July 2014) - Rajappan, Kim; Ginks, Matthew
ABSTRACT: : Catheter ablation of atrial fibrillation (AF) is performed increasingly worldwide and with the development of new technologies the procedures have become safer and more effective after a single attempt, particularly with paroxysmal AF. However, success rates for persistent AF ablation remain far lower than paroxysmal AF and there is large variation in the strategies used worldwide. This review describes the background to persistent AF ablation, the different strategies used and their associated risks and benefits, developing technologies and the authors' perspective on the future of this rapidly evolving area.